Baseline and clinical characteristics of older adults admitted to the intensive care unit through the emergency room: Analysis based on age groups. Issue 2 (March 2021) - Lee, Ye Lim; Ha, Sang Ook; Park, Young Sun; Yi, Jeong Hyeon; Hur, Sun Beom; Lee, Ki Ho; Hong, Ki Yong; Sin, Ju Young; Kim, Duk Hwan; Cha, Jun Kwon; Kim, Jin Hyuck
Background and Objectives: There is currently no consensus on the criteria for admitting older adults to the intensive care unit. Methods: This single-center retrospective study evaluated the baseline and clinical characteristics of older adults admitted to the intensive care unit between January 2017 and June 2017; patients were analyzed according to their age group. Factors associated with in-hospital mortality were specifically determined using logistic regression analysis. Results: Among 582 patients included in the present study, 34.2%, 46.6%, and 19.2% were aged 65–74, 75–84, and over 84 years, respectively. In terms of clinical outcomes, although there were no significant differences in the length of intensive care unit and hospital stay and intensive care unit mortality, significant differences were observed in terms of in-hospital mortality, hospital discharge disposition, and neurologic outcomes at discharge ( p  = 0.039, p  = 0.005, and p  = 0.032, respectively). Predictive factors for in-hospital mortality were age (⩾85 years), initial mental status (stupor to coma), a Korean Triage and Acuity Scale level of 1, underlying diagnosis of cancer, abdominal pain or discomfort, apnea, and a chief compliant of dyspnea. Conclusion: Compared to those aged 65–84 years, in-hospital mortality was 1.96-fold higher in those aged over 84 years. However, the overall mortality in our cohort was not considerably different from that of the younger population. Intensive care unit admission should be considered in selected older adults after evaluating the risk factors for mortality.